Lewis Bases Trigger Intramolecular CH–Bond Activation: (tBu3SiO)2W=NtBu [rlhar2] (tBu3SiO)(κO, κC‐tBu2SiOCMe2CH2)HW=NtBu. Issue 22 (10th May 2013) - Marshak, Michael P.; Rosenfeld, Devon C.; Morris, Wesley D.; Wolczanski, Peter T.; Lobkovsky, Emil B.; Cundari, Thomas R.
Abstract: The symmetry‐forbidden cyclometalation of (silox)2 W=N t Bu (1, silox = OSi t Bu3 ) to (silox)( t BuN)W(H)(κ O, κC‐OSi t Bu2 CMe2 CH2 ) (2 ) was investigated by kinetics [Δ H ‡ = 19.2(9) kcal/mol; Δ S ‡ = –23(3) eu; Δ G ‡ (25 °C) = 26.1(10) kcal/mol], isotopic labeling {[D54 ]1 → [D54 ]2 ; k H / k D = 2.7(4)}, and equilibrium studies [Δ H ° = –6.7(3) kcal/mol; Δ S ° = –12.1(8) eu; Δ G °(25 °C) = –3.1(4) kcal/mol]. The crystal structure of2 reveals a pseudo‐square‐pyramidal structure that can be viewed as a distorted tetrahedron with the W–H and W–C bonds occupying one site. The addition of H2 (or D2 ) to1 proceeds similarly to afford (silox)2 ( t BuN=)WH2 (3 ), and the addition of H2 to2 also affords3, but labeling experiments show that it proceeds via1 . Phosphane bases with cone angles < 160° trigger the cyclometalation of1 to2 in < 5 min, and PMe3 catalyzed the dihydrogen addition to1 . Quantum mechanics/molecular mechanics (QM/MM) calculations support the experimental findings and show that Lewis bases promote σ/π mixing. The experimentally observed intermediate (silox)2 ( t BuN=)WPMe3 (1 ‐PMe3 ) has a (d yz ) 2 (i.e., π 2 ) ground state in contrast to the (d   z   2 ) 2 (i.e., σ 2 ) configuration of1 . The σ/π mixing circumvents the constraints of orbital symmetry for both cyclometalation and dihydrogen addition. Abstract : The symmetry‐forbidden cyclometalation of (silox)2 W=N t Bu (1, silox = OSi t Bu3 ) to (silox)( t BuN)W(H)(κ O, κ C‐OSi t Bu2 CMe2 CH2 ) (2 ) and the oxidative addition of dihydrogen to give (silox)2 ( t BuN=)WH2 (3 ) are catalyzed by phosphane bases with cone angles < 160°. Quantum mechanics/molecular mechanics (QM/MM) calculations support the experimental findings and show that Lewis bases promote σ/π mixing.